ANALISIS DAYA GENERATOR MAGNET PERMANENT DALAM SKALA LAB UNTUK PROTOTIPE PEMBANGKIT LISTRIK TENAGA ARUS LAUT - Egi Riansyah; Puteri Islamega Taufani; yudhi; Zanu Saputra (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The entry of electrical energy in Indonesia relies on fossil energy, which is non-renewable energy. Where over time this energy production will decrease and increase natural damage. Therefore, it is necessary to use renewable energy such as ocean current energy, where the potential of this energy in generating electrical power in Indonesia is 17.9 GW. This potential is used to manufacture a prototype of a marine current power plant (PLTAL), where the advantage of this prototype is to use a permanent magnet DC generator which has the advantage that it can be operated without paying attention to frequency stability, so it does not need a governor. The purpose of this study is to analyze the power generated by a permanent magnet DC generator with the rpm value obtained from the DC motor which will later be used as a reference in the PLTAL prototype. The research method used is a quantitative method, by conducting a literature study, designing and compiling the working concept of the tool, testing the tool and collecting data, and the last stage is analysis. The minimum power generated by a permanent magnet generator with a source from a DC motor rotation is 1.55 Watt and the maximum power generated is 12.87 Watt. Permanent magnet DC generator that uses Neodymium (NdFeB) magnets arranged tightly around the rotor can produce a strong induced magnetic field in converting mechanical energy into electrical energy.